Medical equipment in the global south: perspective of sustainability and donations - Paustian, Frederik; Gøl, Rasmus; Wolfe Julsgart, Hannah; Bjerre Degn, Sofie; Philip Rosenbom, Andreas; Aaby Henriksen, Anton; Højgaard, Liselotte (Frontiers in Health Services, 2025)
Disparities in healthcare infrastructure between the Global South and North continue to affect medical equipment availability, functionality, and sustainability in low- and middle-income countries (LMICs). This study combines a systematic literature review with on-site fieldwork in Ugandan hospitals to assess the current state of medical equipment in LMICs and propose actionable strategies for more sustainable donation practices. Following a systematic literature review, 18 articles were analyzed and categorized according to five research questions addressing sustainability metrics, affordability, recycling practices, systemic barriers, and innovations in medical equipment use. Parallel fieldwork conducted by biomedical engineering volunteers in two Ugandan hospitals documented over 1,400 devices and resulted in the repair of 51 items—generating estimated savings of $102,000. Many devices remained unused due to a lack of spare parts and contextual compatibility. A carbon footprint assessment of donated equipment shipment from Denmark to Uganda further underscored the environmental implications of donation programs. Drawing on literature insights and field observations, this paper proposes a set of eight principles to enhance the sustainability and long-term impact of medical equipment donations. Emphasizing context-aware design, training, maintenance, and donor-recipient collaboration, these recommendations aim to shift donation models toward more resilient and responsible healthcare partnerships.